Addition of Aβ42 to Total Cerebral Small Vessel Disease Score Improves the Prediction for Cognitive Impairment in Cerebral Small Vessel Disease Patients - Liu J (Dove Medical Press, 2021)
Jianping Liu,1 Weihua Zhao,2 Qinghong Gui,1 Ying Zhang,1 Zaiyu Guo,2 Wei Liu3 1Department of Neurology, Tianjin TEDA Hospital, Tianjin 300457, People’s Republic of China; 2Department of Neurosurgery, Tianjin TEDA Hospital, Tianjin 300457, People’s Republic of China; 3Department of Neurology, Tianjin Medical University General Hospital, Tianjin 300052, People’s Republic of ChinaCorrespondence: Zaiyu GuoDepartment of Neurosurgery, Tianjin TEDA Hospital, No. 65, The Third Avenue, Tianjin Economy Development Area, Tianjin 300457, People’s Republic of ChinaTel +86-15302100230Email guozaiyu_teda@163.comWei LiuDepartment of Neurology, Tianjin Medical University General Hospital, No. 154, An Shan Road, Heping District, Tianjin 300052, People’s Republic of ChinaTel +86-2260362255Email liuweithird@126.comPurpose: To investigate the associations between concentrations of Aβ40 and Aβ42 and vascular cognitive impairment (VCI) in cerebral small vessel disease (CSVD) patients and evaluate the value of combination of levels of Aβ40 or Aβ42 and the total CSVD score in predicting VCI.Patients and Methods: A total of 199 CSVD patients were divided into VCI group and non-VCI group according to the criteria of VCI. Demographic data, MRI markers of CSVD, blood pressure, vascular risk factors, laboratory markers, and serum Aβ40 and Aβ42 concentration were collected. Univariate analysis was performed with the Student’s t-test, Mann–Whitney U-test or Chi-square test. Variables with P< 0.10 in univariate analysis were then included in multivariate analysis that used a backward stepwise logistic regression model. The predictive values were assessed with receiver operating characteristic (ROC) curve.Results: VCI was determined in 112 CSVD patients (56.3%). Hyperlipidemia (OR: 1.618, 95% CI: 1.265– 3.049), the total CSVD score (OR: 1.414, 95% CI: 1.213– 2.278) and serum Aβ42 concentration (OR: 1.401, 95% CI: 1.212– 1.946) were independent risk factors for VCI in CSVD patients with adjustment for age, education years, diabetes and fasting blood-glucose (FBG). The area under curves (AUCs) were 0.640 (SE: 0.040, 95% CI: 0.563– 0.718), 0.733 (SE: 0.035, 95% CI: 0.664– 0.802) and 0.827 (SE: 0.030, 95% CI: 0.768– 0.887), respectively, for the total CSVD score, serum Aβ42 concentration and their combination applied in predicting VCI in CSVD patients. Z test demonstrated that the AUC of combination prediction was significantly higher than individual prediction (0.827 vs 0.640, Z=3.740, P< 0.001; 0.827 vs 0.733, Z=2.039, P=0.021).Conclusion: Combination of Aβ42 and total CSVD score could significantly elevate the predictive value of cognitive impairment in CSVD patients.Keywords: Aβ40, Aβ42, vascular cognitive impairment, cerebral small vessel disease, total cerebral small vessel disease score